2020
DOI: 10.1136/bmjoq-2018-000533
|View full text |Cite
|
Sign up to set email alerts
|

Reducing readmissions and improving patient experience following urological surgery, through early telephone follow-up

Abstract: Readmission from urological surgery is common, with a readmission rate for day case surgery of 3.7% and 26% for robot-assisted cystectomy. Readmission to secondary care and representation to primary care are both expensive and preventable. This project aimed to reduce both and also enhance the care of patients following urological surgery in a large tertiary referral centre, within the National Health Service. A retrospective telephone follow-up (TFU) survey was set up in the early postoperatively period to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Although our brain tumor center treats mostly non-emergent patients (94%) with a high proportion of patients with prior surgery (25%), our pathology mix is similar to that of other centers and trends with national brain tumor demographics [25]. Additionally, while our findings are specific to patients with primary and secondary brain tumors, many of these measures are relevant and applicable to other specialties and are already being implemented in some centers [44,47,48,53,54].…”
Section: Future Enhancements and Generalizability Of This Paradigmmentioning
confidence: 67%
See 1 more Smart Citation
“…Although our brain tumor center treats mostly non-emergent patients (94%) with a high proportion of patients with prior surgery (25%), our pathology mix is similar to that of other centers and trends with national brain tumor demographics [25]. Additionally, while our findings are specific to patients with primary and secondary brain tumors, many of these measures are relevant and applicable to other specialties and are already being implemented in some centers [44,47,48,53,54].…”
Section: Future Enhancements and Generalizability Of This Paradigmmentioning
confidence: 67%
“…However, the protocol we implemented early in the pandemic allowed us to still bring patients to surgery and rapidly and safely discharge them. We postulate, as others have shown, that more extensive patient education and expectation management of their ability to safely leave the hospital helped in this effort [47,48]. Patient motivation in minimizing their hospital stay has helped facilitate these changes, which would have previously been met with a level of reluctance.…”
Section: Pandemic-induced Enhancements Of Patient Preparation Education and Team Engagementmentioning
confidence: 82%
“… 8 , 10 Telephone calls to patients as a follow-up has been shown to be associated with reduced readmission rates of up to 80% among discharged patients after surgery. 7 A previous study at our institution established that patients preferred telephone follow-up clinics to in-person outpatient visits. 15 There is evidence, however, that text messages are preferred over other forms of communication because of their simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth is less expensive for health-care providers, and for recipients, and improves health-care access 4 , 5 while reducing avoidable readmissions, emergency department visits, and overtime reimbursements. 6 , 7 The benefits of telemedicine have been observed across a range of different specialities 8 , 9 , 10 , 11 , 12 , 13 , 14 and for surgical outpatient services. 9 , 15 , 16 , 17 Patients also associate telehealth follow-up, especially text messaging, with increased information retention.…”
Section: Introductionmentioning
confidence: 99%
“…Nurse-led telephone follow-up is the most frequently used approach for providing follow-up care that includes individual health guidance and psychological support. Telephone follow-up has already been introduced for patients in various settings, including follow-up after urological surgery, cataract surgery, Mohs micrographic surgery, pelvic floor surgery, and for patients experiencing obstructive sleep apnea [ 9 13 ]. Research has shown that health care quality and the burden of postoperative symptoms or patient satisfaction could improve if patients receive telephone follow-up [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%